PEMANFAATAN MEDIA SOSIAL WAG DALAM PJJ MODA DARING MASA DARURAT COVID-19 DI UPTD SPF SDN GRUJUKAN 2 CERMEE TAHUN PELAJARAN 2020/2021: UPTD SPF SDN GRUJUKAN 2 CERMEE - EKO AGUSRINI (Dewan Pendidikan Bondowoso, 2022)
The spread of the Corona Virus Disease (COVID - 19) outbreak is a complex problem at UPTD SPF SDN Grujukan 2. The limited ability of parents to own devices is a vital problem for teachers in implementing PJJ, students are required to participate in online learning. In the readiness of device ownership in implementing PJJ, not all parents have their own devices in online learning via WhatsApp Group. Of the 4 5th grade students, only 1 person does not have a gadget. However, students who do not have these devices can still study in groups with their friends who have devices. The objectives of this study are: 1) To describe the use of WAG Social Media in PJJ during the Covid-19 pandemic at UPTD SPF SDN Grujukan 2 Bondowoso in the 2020/2021 academic year. 2) Analyzing the impact of using WAG Social Media in PJJ during the Covid-19 pandemic on student learning outcomes of UPTD SPF SDN Grujukan 2 Bondowoso for the 2020/2021 academic year. 3) Want to know how much the use of WAG Social Media in PJJ during the Covid-19 pandemic on student learning outcomes UPTD SPF SDN Grujukan 2 Bondowoso for the 2020/2021 academic year. The benefits of this research for all parties, namely: 1) Providing educational services for students during the covid-19 pandemic, 2) Teachers using various platforms, one of which is using WAG in distance learning during the covid-19 pandemic, 3) Improving the quality of education during the covid-19 pandemic, 4) helping parents whose economy is middle to lower while studying from home. This research was conducted at UPTD SPF SDN Grujukan 2 Cermee District, Bondowoso Regency. The subjects of this study were teachers at UPTD SPF SDN Grujukan 2 which consisted of 3 male teachers and 6 female teachers. This research was carried out in the odd semester of the 2020/2021 school year starting from September 2020 to November 2020. Suharsimi Arikunto (2006), divided into 4 stages of classroom action research, namely: 1) Planning (planning), 2) Implementation (action), 3 ) Observation (observation), 4) Reflection (reflection). The conclusion of the research on the use of WAG in online-mode distance learning at UPTD SPF SDN Grujukan 2, from the results of the supervision carried out by the Principal, in the 1st supervision of teachers who carried out online learning only 88%, student responses 55% and material achievement 69 %. While the results of the 2nd supervision there is an increase in online mode learning, namely teachers who carry out online learning to 100%, meaning that all teachers carry out online learning. Meanwhile, students' responses to online learning through WAG increased to 78% and the achievement of learning materials was 81%